Metode Analitychal Hierarchy Process Dan Simple Multi Attribute Rating Technique Sebagai Penunjang Keputusan Pemilihan Supplier - Bayu Aji Setiyawan; Sri Siswanti; Muhammad Hasbi (STMIK Sinar Nusantara, 2020)
Process of choosing a supplier in Sukoharjo has not used the application program in making the decision but still use the manual way in writing. In addition, in conducting the selection of suppliers conducted by the HRD section is still subjective so that the results obtained in the selection of suppliers are less valid because in selecting HRD suppliers only choose based on price criteria, where If there is a supplier that offers the lowest price then the supplier will be chosen as a supplier in Sukoharjo. The purpose of the research is to build and implement a decision support system that is useful for the selection of suppliers in Sukoharjo using the method of Analyitychal Hierarchy Process (AHP) and Simple Multi Attribute Rating Technique (SMART). Where AHP method to calculate the weight of the criteria and SMART method to calculate the supplier's alignment. With testing black box system is already running according to the function and for the results of the validity test get the test value results in the category very good with a percentage of 80%.